Publication Planning 101 - Sergio Sismondo; Scott Howard Nicholson (Frontiers Media S.A., 2009)
Question: This article is a report on a meeting of "publication planning", the organizational and practical work that shapes pharmaceutical companies' data and eventually turns it into medical journal articles, especially those reporting on clinical trials. Material and Methods: Our report is primarily based on information presented at the 2007 annual meeting of the International Society of Medical Planning Professionals (ISMPP) attended by one of us, including a workshop entitled "Publication Planning 101/201". The article is a narrative review based on statements made at the 2007 ISMPP meeting, on advertisements by publication planning agencies, and on previous reports and background literature. Findings: We argue that the main purpose of publication planning is to create and communicate scientific information to support the marketing of products. We provide some analysis of the role of publication planning in medical publishing, and its implications for the structuring of medical knowledge. Medical literature relevant to current drugs is to a large extent shaped by commercial interests.